ACCESSIBILITY AND CONNECTIVITY ANALYSIS IN THE GROWING RURAL AREA: A CASE STUDY OF REMBAU DISTRICT, NEGERI SEMBILAN - Mohd Yusoff, Zaharah; Md Ramlan, Norazrina; Mohd Salim, Pauziyah; Mohsin, Aminah; Mohd, Mazlan; Sri Mulyawati, Lilis (PLANNING MALAYSIA, 2023)
Rural areas are the ideal place to handle urban sprawl, whether for future administrative, college, manufacturing, residential, commercial, or for business growth. In the land development context, the shifting from rural into several areas such as agricultural into houses or subdividing real estate into commercial lots etc. were seen to be worth trying. However, this will succeed with the help of better road connectivity to the demanded area. This research is aimed to explore the road accessibility and connectivity and its function in supporting the growth of land development in Rembau, Negeri Sembilan. The research methodology produces maps of new potential growth development areas using GIS techniques. For data acquisition, there was a two-approach which is using the primary and secondary data. The primary data consist of the observation on the site, interview method with the experts and local people. Meanwhile, the secondary data is using the Landsat data from USGS to produce a land-use map for four consecutive years, base map and route connectivity data for GIS method, and statistical data from related agencies. The result of this research is to produce a new potential development map in Rembau, Negeri Sembilan. Remote sensing (RS) and Geographical Information System (GIS) allows the town planners to identify the potential rural spaces to cater the urban population.